2012
DOI: 10.1136/bjophthalmol-2011-301263
|View full text |Cite
|
Sign up to set email alerts
|

Review of endophthalmitis following Boston keratoprosthesis type 1: Table 2

Abstract: Endophthalmitis remains one of the most damaging and challenging complications following Boston keratoprosthesis type 1 (KPro) surgery. The authors reviewed the literature from 2001 onward to identify cases of endophthalmitis following KPro surgery and present an additional case of endophthalmitis in a patient with Stevens Johnson syndrome. The prevalence of endophthalmitis between 2001 and 2011 was 5.4%. Gram-positive bacteria are the most common agents responsible for endophthalmitis in this patient populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 35 publications
0
68
0
Order By: Relevance
“…Current strategies for combating implant-associated ocular infections include the continuous use of topical antibiotics (1). However, a serious concern regarding the continuous use of conventional antibiotics is the potential development of antibioticresistant pathogens such as methicillin-resistant Staphylococcus aureus (MRSA) (35)(36)(37) and fungi (7). Antibiotic-resistant infections can lead to devastating effects and uncontrolled bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current strategies for combating implant-associated ocular infections include the continuous use of topical antibiotics (1). However, a serious concern regarding the continuous use of conventional antibiotics is the potential development of antibioticresistant pathogens such as methicillin-resistant Staphylococcus aureus (MRSA) (35)(36)(37) and fungi (7). Antibiotic-resistant infections can lead to devastating effects and uncontrolled bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…The rabbits developed a more severe keratitis after P. aeruginosa inoculation than after S. aureus inoculation, even without the presence of AMP. However, the superior efficacy against S. aureus is clinically advantageous, since S. aureus is the leading cause of endophthalmitis and bacterial keratitis after ocular implantation (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A combined analysis of data from 12 retrospective case series and two case reports from 2001e2011 reported an overall prevalence of endophthalmitis of 5.4% and found that the prevalence dropped substantially from 2001 (12%) to 2007 (2.3%) with use of topical vancomycin. 77 In a large retrospective study of 255 eyes, the incidence of bacterial endophthalmitis was 0.35% per patient-year in a vancomycin treated group, but 4.13% in those who had not received vancomycin. 30 A series of 126 eyes, all on topical vancomycin and a fourth generation fluoroquinolone, found an incidence of endophthalmitis of 2.4%, or 0.014 infections per patient-year.…”
Section: Infectious Endophthalmitismentioning
confidence: 98%
“…13,53 Other clinical signs include fibrin, donor corneal edema, retinal periphlebitis, and lid swelling. 77 Pathogens implicated in bacterial endophthalmitis prior to the advent of vancomycin prophylaxis were largely grampositive, marked by a predominance of Streptococcus pneumoniae, other Streptococcus species, Staphylococcus aureus, and coagulase-negative Staphylococcus. 66 With the wide usage of topical vancomycin prophylaxis, gram-positive pathogens have become less common, with fungal and gram-negative bacteria now more frequently implicated.…”
Section: Infectious Endophthalmitismentioning
confidence: 99%